TriloMorph: a dynamic and collaborative database for morphogeometric information of trilobites - Serra, Fernanda (2023)
Two files are attached, one related to the first version of TriloMorph (Stable_release_1.0), and another containing the codes and files related to the script, such as information of Devonian occurrence of trilobites from the PBDB and R codes (TriloMorph_Serra et al.).